The Aplication of TAI Learning Model Based on PBI to Increase Activity and Mathematics Learnings Outcomes - Hadi Wahyudi; Tri Novita Irawati; Fury Styo Siskawati (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2021)
Abstrack This study aims to improve student activity and learning outcomes through the TAI learning model based on PBI. This type of research is Classroom Action Research (CAR). The research subjects were students of class VIII SMP An-Nisa Gumukmas. The data collection methods used were interview, observation, test and documentation methods. This research was conducted in two cycles. Based on the results of the research that has been done, the percentage of activity in the first cycle is 56.71% and in the second cycle it is 71.99%, that there appears to be an increase. Then for the average value in cycle I is 68.89 with a percentage of learning outcomes completeness of 55.56% and in cycle II an average value of 78.67 is obtained with a percentage of 92.59%, this shows that there appears to be an increase in activity and student learning outcomes by applying the TAI learning model based on PBI. From the results obtained, it can be concluded that the application of the TAI learning model based on PBI can increase student activity and learning outcomes. Keywords: TAI, PBI, learning activity, learning outcomes